Analysis of the Effect of Work Environment and Organizational Culture on Teacher Performance with Teacher Work Discipline as an Intevening Variable - Mintaasih Utami; Muchlis H Mas'ud (Journal of Management Research and Studies, 2023)
This study aims to analyze the effect of work environment and organizational culture on teacher performance in the context of Vocational High School Education Institutions in Sumberpucung District, Malang Regency. The research method used is a quantitative research method with an explanatory research approachThe collected data were analyzed using the multivariate Structural Equation Models (SEM) model with the Partial Least Square (PLS) approach. SmartPLS version 3 software is used to process data and test hypotheses. The results showed that the work environment and organizational culture had a positive influence on the work discipline of teachers at SMK Education Institutions in Sumberpucung District, Malang Regency. Furthermore, the work environment and organizational culture are also positively related to improving teacher performance. Although work discipline has a positive effect on teacher performance, this effect is not directly significant. However, it was found that work discipline acts as a mediating variable between work environment and teacher performance, and between organizational culture and teacher performance. Thus, a good work environment and organizational culture can improve teacher work discipline, which in turn improves teacher performance in these educational institutions.